FRAUD DIAMOND TERHADAP KECURANGAN AKADEMIK - meliana, rini; Setiawan, Aris; Aida Qur’an, Amanah (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
The purpose of this research to analyze the factors that influence academic cheating onundergraduate students majoring in accounting. This research analyzes the effect of pressure,rationalization, capability and opportunity (fraud diamond) on academic fraud. The method usedin this research is the experimental method and uses primary data in the form of a questionnaire.The research respondents were 200 students of the Accounting undergraduate study program atPanca Bhakti University Pontianak. The sampling method used purposive sampling. While theanalytical tool used is SmartPLS with a bootstrap approach in statistical testing. The resultsshowed that pressure had no effect on academic fraud. Meanwhile, rationalization, capability andopportunity had affect on academic cheating.